A critical analysis on the Status & Recognition of Jual Janji Customary Security transaction in Malaysia / Ahmad Aliff Mashuri … [et al.] - Mashuri, Ahmad Aliff; Ramli, Muhammad Shazwan; Mohamad Tajudin, Nordiana; Hashnan, Nur Syakirah (2013)
The topic of our research is "A Critical Analysis on the Status & Recognition of Jual Janji Customary Security Transaction in Malaysia". The purposes of this research are to identify the relevancy of the principle of jual janji in Malaysia and to identify its real status due to inconsistencies of judgments by the courts. This research also aim to identify the problems regarding the principles of jual janji in Malaysia, to analyzed and decide whether jual janji customary transaction is suitable and relevant to be applied in the modern era of Malaysia and to determine what are the effects and outcomes of the application of jual janji is principles in Malaysia. This research was conducted by referring to the cases involving the principles and writings that are related to this research. By conducting this research, we hope that there will be a definite status of the principle so that the people who are still practicing the principle will not lead to any confusion due to its vague status. This research will also assist the judiciary in delivering judgments in cases regarding the principle if it arises in the future.